Kepastian hukum permohonan imbalan bunga terhadapKelebihan pembayaran surat tagihan pajak atas denda penagihan - Janas, Anferdi; Sartono, Sartono; Ismed, Mohamad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
Legal certainty in tax regulations must be stipulated in the Law clearly and not open to multiple interpretations, this aims to ensure that taxpayers obtain legal certainty in carrying out their tax obligations and protect their rights as taxpayers, who have contributed greatly to building the Indonesian state. One of the rights of taxpayers is to receive interest compensation if there is an excess payment of tax that has been paid by taxpayers to the state, in its implementation taxpayers often experience obstacles regarding the interpretation of the applicable formal provisions when submitting an application for interest compensation to the Director General of Taxes, the application for interest compensation in question relates to excess payments on tax bills for fines related to fines for collection of Article 27 paragraph (5d) in the Law on General Provisions and Tax Procedures, due to an appeal decision that rejects the application from the Taxpayer which causes an increase in the Taxpayer's tax burden, taxpayers can still take legal action for a judicial review to the Supreme Court if they are not satisfied with the appeal decision, In the event that the legal action for a Judicial Review from the taxpayer is granted in whole or in part, the collection fine must be returned to the taxpayer, but can interest compensation be requested from the collection fine? In this study, the researcher uses the Legal System Theory and the Legal Certainty Theory as research analysis tools to be able to answer the problems in the research object. This research uses a normative juridical research method which looks for data in the form of statutory regulations and Tax Court decisions regarding requests for interest compensation for excess payment of tax bills over collection fines. So this research aims to find out how the application for interest compensation is implemented. regarding tax overpayments and legal certainty regarding requests for interest compensation regarding overpayments of tax invoices over collection fines Legal certainty regarding the request for interest compensation on excess tax bill payments on fines for collection of collection still needs further confirmation because in the Tax Bill there are many forms of Administrative Sanction fines. The Request for Interest Compensation on Excess Tax Payments should create regulations that can shorten the time and are easy to understand for all taxpayers in order to make it easier for taxpayers to fulfill their tax obligations.